EXPERIMENTAL KINETIC STUDY OF THE SMECTITE-TO-ILLITE TRANSFORMATION - Cuadros J.; Linares J. (My University, 1996)
The <20 µm size fraction of a bentonite from the serrata de nijar deposit (almeria, southeastern spain) was hydrothermally treated to study kinetics smectite-to-illite transformation, in order estimate performance life barrier high level nuclear waste repository. studied consisted randomly interstratified illite montmorillonite with 15% illite. minor amounts other minerals (3% quartz, plagioclase, and cristobalite)were also present. run conditions hydrothermal treatments combinations following variables: kcl concentration 0.025, 0.05, 0.1, 0.3, 0.5, 1 mol l-1; temperature 60, 120, 175, and 200°C; time 1, 5, 15, 30, 90, and 180 days. The solid: solution ratio was 1:5. Pressures were those corresponding to water vapor. The solid reaction products were analyzed by means of XRD, DTA/TG, FTIR, and NMR. The final solutions were chemically analyzed for Si and exchange cations (K, Ca, Mg, and Na), and pH. XRD detected some transformation (up to 15%), while DTA/TG, FTIR, NMR, and exchange cation analysis did not show any appreciable transformation. This leads to the conclusion that analysis of the amount of illite in illite/smectite, in hydrothermally treated samples, by means of XRD can be inaccurate. Transformation to illite was observed, however, when aqueous silica concentrations were examined. These concentrations yielded the kinetic expression -dSdt = kK1Sn , where S is the fraction of smectite in illite/smectite, t time, k the rate constant, and K potassium concentration in solution. The exact value for n could not be determined, although data from this and other studies suggest n > 1. The activation energy of the process is #7 kcal mol-1, suggesting a solid transformation mechanism. Based on these results, smectite seems to offer a safe barrier for nuclear waste.